Aromaticity Determines the Relative Stability of Kinked vs. Straight Topologies in Polycyclic Aromatic Hydrocarbons - Poater, Jordi; Duran, Miquel; Solà, Miquel (Frontiers in Chemistry, 2018)
It is well-known that kinked phenacenes are more stable than their isomeric linear acenes, the archetypal example being phenanthrene that is more stable than anthracene by about 4–8 kcal/mol. In previous studies, the origin of the higher stability of kinked polycyclic aromatic hydrocarbons (PAHs) was found to be better π-bonding interactions, i.e., larger aromaticity, in kinked as compared to linear PAHs. Some years ago, however, Dominikowska and Palusiak (Phys. Chem. Chem. Phys. 2011, 13, 11976) found that dicationic linear anthracene is more stable than the dicationic kinked phenanthrene. Therefore, these authors showed that, in some cases, the linear topology in PAHs can be preferred over the kinked one. Our results using energy decomposition analyses in combination with the turn-upside-down approach show that the origin of the higher stability of dicationic anthracene is the same as in the neutral species, i.e. better π-bonding interactions. A similar result is found for the kinked and straight tetramethylated-pyrano-chromenes. We conclude that the aromaticity is the driven force that determines the relative stability of kinked vs. straight topologies in PAHs.